Occurrence of the Association contagious ecthyma (ORF virus) in sheep with these animals' caregivers - Ferreira, B. L. S. [UNESP]; Silva, D. T. [UNESP]; Pituco, E. M.; Ribeiro, C. P.; Okuda, L. H.; Victoria, C. [UNESP]; Pantoja, J. C. F. [UNESP]; Modolo, J. R. [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2016)
These diseases are all widespread in the State of Sao Paulo. 42 (8.64%) animal caregivers and 444 (91.36%) sheep (n=486) were sampled. The reagents Prevalence paragraph virus neutralization was 67% (95% CI = 62-71%) in sheep and 76% (95% CI = 63-89%) for caregivers, with P=0.22 not being a statistically significant difference between the species. One of the distribution titles had significant difference between statistics as species with P=0.0048. The titration variations were 0.6 to 2.1, both in sheep and their caregivers. Among the 42 sheep caregivers participating in the study, 32 had antibody securities denominated in log(10) above 0.6.
Keywords: ORF virus; virus neutralization; animals; humans